Show and Tell Sebagai Metode Belajar Literasi Siswa di Dalam Kelas - Suharti Sirajuddin; Reni Safitri; Maria Enjelina Debibilian (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the work programs for Class 6 Teaching Campus students is the show and tell method as a literacy learning material at the Muhammadiyah 1 LP Layang Elementary School, Makassar City, South Sulawesi. This activity aims to help students improve literacy and numeracy. Apart from that, students also prepare work programs to help schools, especially in classroom learning. This program is expected to have a positive impact on schools by honing students' skills in writing, reading, and speaking. Apart from that, by collaborating between teachers and students, the Teaching Campus can develop students' insight, character, and soft skills; increasing the role and real contribution of universities and students in national development. The impact felt by students as long as the Teaching Campus students accompany teachers in teaching in class is an increase in the percentage of motivation and interest in learning by around 70-80%. Teaching Campus teachers and students are required to be able to design learning activities from planning to evaluation in a simpler, creative and effective way. Teaching Campus students and teachers at schools also work together as partners in preparing, tidying up and completing the principal's administration. This aims to make it easier for schools to improve school quality.